Respuesta :

Answer:

[tex]\textsf{Apply the Perfect Square Formula}\quad (a + b)^2 = a^2 + 2ab + b^2:[/tex]

[tex]\implies (a+bi)^2=a^2+2abi+(bi)^2[/tex]

[tex]\textsf{Apply exponent rule} \quad (a\cdot b)^c=a^cb^c:[/tex]

[tex]\implies a^2+2abi+b^2i^2[/tex]

[tex]i=\sqrt{-1} \implies i^2=-1[/tex]

[tex]\textsf{Apply imaginary number rule} \quad i^2=-1:[/tex]

[tex]\implies a^2+2abi+b^2(-1)[/tex]

[tex]\implies a^2+2abi-b^2[/tex]

[tex]\textsf{Collect the real parts:}[/tex]

[tex]\implies a^2-b^2+2abi[/tex]

[tex]\textsf{Factor the real parts by applying the Difference of Two Squares Formula}\\x^2-y^2=(x+y)(x-y) :[/tex]

[tex]\implies (a+b)(a-b)+2abi[/tex]

LHS

  • (a+bi)²
  • (a+bi)(a+bi)
  • a²+b²i²+2abi
  • a²-b²+2abi

RHS

  • (a+b)(a-b)+2abi
  • a²-b²+2abi

Hence verified

ACCESS MORE